Perancangan Antarmuka Q-Commerce Multi-Vertical Dengan Pendekatan Human-Centered Design Untuk Digitalisasi UMKM - Saliyah Macky (LKP Unity Academy, 2025)
The growth of E-commerce in Indonesia has driven the emergence of Quick Commerce (Q-commerce), a location-based business model offering instant delivery services. However, existing platforms remain limited to specific product categories and are unable to accommodate urgent multi-vertical needs. This study aims to design a multi-vertical Q-commerce application interface using the Human-Centered Design (HCD) approach, consisting of three phases: inspiration, ideation, and implementation. The inspiration phase was conducted through comparative studies, interviews, and user questionnaires. The ideation phase produced functional requirements and a visual prototype using Figma. The implementation phase evaluated the prototype using the System Usability Scale (SUS) questionnaire. The results produced a SUS score of 75,92, falling under the Good and Acceptable category, suggesting that the designed interface is well-received and usable by the target users